Crossing cultures : creating identity in Chinese and Jewish American literature - Oster, Judith (University of Missouri Press, 2003)
"In this important new study, Judith Oster looks at the literature of Chinese Americans and Jewish Americans in relation to each other. Examining what is most at issue for both groups as they live between two cultures, languages, and environments, Oster focuses on the struggles of protagonists to form identities that are necessarily bicultural and always in process. Recognizing what poststructuralism has demonstrated regarding the instability of the subject and the impossibility of a unitary identity, Oster contends that the writers of these works are attempting to shore up the fragments, to construct, through their texts, some sort of wholeness and to answer at least partially the questions Who am I? and Where do I belong?"--Jacket